The effect of AI-assisted problem-oriented project-based learning on students’ critical thinking and communication skills - Laila Badriyatul Habibah; I. Ibrohim; Herawati Susilo (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Education 4.0 has emerged as a response to the Industrial Revolution 4.0, focusing on integrating technology into learning to support digital transformation and enhancing 21st-century skills, such as critical thinking, creative thinking, communication, and collaboration. While technology provides convenience, it also challenges students to develop these essential skills. An innovative model, such as Problem-Oriented Project-Based Learning (POPBL), is required to improve these skills, as it has been proven effective in enhancing 21st-century skills. The incorporation of artificial intelligence is expected to increase the effectiveness of POPBL. This study aims to evaluate the impact of the POPBL-AI model on students' critical thinking and communication skills. It employs a quasi-experimental design with a non-randomized pre-post-test control group format. Three groups participated in the study: the POPBL-AI, POPBL, and PBL classes. Data were collected through essay tests and questionnaires, both of which have been validated and are reliable. Data were analyzed using Analysis of Covariance (ANCOVA), alongside homogeneity and normality tests as prerequisites. The results showed a significant positive effect of the POPBL-AI model on both skills (p = 0.000; p = 0.001). These findings suggest that the POPBL-AI model can be effectively implemented in biology learning to enhance students' 21st-century skills.